The role of food from natural resources in reducing vulnerability to poverty: a case study from Zimbabwe - Festus Akinnifesi; Hermann Waibel; Dagmar Mithöfer (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
Vulnerability to poverty is a major problem in the rural areas of Sub Saharan Africa. Rural Households are confronted with various covariate and idiosyncratic shocks and are often severely constrained in coping with such events. They frequently resort to food from natural resources such as indigenous fruits during times of crisis. The availability of such food sources is increasingly at risk due to deforestation and biodiversity loss. The objective of this paper is to quantify the contribution of indigenous fruit trees towards reducing vulnerability to food insecurity and poverty. The methodology used is a multi-period stochastic household income model. The data were collected in a case study in Zimbabwe using detailed monthly income and expenditure records of a sample of 39 rural households in two areas. The two regions differ in their agricultural system. In one area horticulture, off-farm activities and exotic fruits are a major source of income while in the other area indigenous fruits are a more important source of income. This paper concentrates on the latter area. Model calculations show that rural households in Zimbabwe are highly vulnerable to seasonal fluctuations in income and therefore a critical period where households run high risk of being food insecure can be identified. While indigenous fruits, as a low cost natural resource, can facilitate income smoothing, the role of other sources of income must not be neglected. The paper concludes that diversified season-specific income generating portfolios must be designed of which indigenous fruit trees have a role to play.
Keywords: 330; Vulnerability; poverty; food security; seasonal fluctuations; wild food resources; Zimbabwe